Geopolitical Trends and Need for Coherent Foreign and Security Policy for Nepal - Sharma, Suresh (Journal of Foreign Affairs, 2022)
Nepal faces a severe geopolitical threat because of the geostrategic position between India and China. This geographical positioning and the constantly changing geopolitical trends seriously impact the country. A comprehensive and coherent foreign and security policy is needed by Nepal to address the risks and threats. Realizing the evolving geopolitical effects on Nepal and the country needs to be ready with the foreign policy and security policy harmonize and coordinate the two to promote and protect the national interest. The study aims to point out the geopolitical threats for the country and recommends the fundamentals for developing a coherent and integrated foreign policy. To justify this necessity, the study explores the relationship between foreign policy and security policy and establishes an interdependent connection between the two. The article also traces the historiography of the harmonious and integrated foreign and security policy of Nepal from the nation-building phase. It identifies the situations in which the country had deviated from the core fundamentals of the foreign and security policies. Methodologically, the article has adhered to the secondary resources and has adopted a qualitative approach to collate and analyze the information thematically.